THE EFFECT OF USING FOAM MORTAR AS AN ALTERNATIVE BACKFILL MATERIAL ON SHEET PILE WALLS ON SLOPES - Auliya Nusyura Al Islami; Faisal Nizar (International Journal of Civil Engineering and Infrastructure, 2023)
Foam Mortar is one of the newest technologies in road and Bridge. The density of foam mortar is only about 40% of the soil or rock, making it a lightweight fill material that significantly reduces lateral and vertical pressure when used as a retaining wall backfilling material. This paper aims to analyze the effect of using foam mortar as backfill material on the performance of sheet pile retaining wall relating to safety factor, bending moment, and sheet pile displacement. Comparative analysis using soil and foam mortar as backfill material is also studied. The modeling is carried out using finite element software with loose sand and foam mortar as the comparative backfill material parameters, and using simple slope model with variations in slope ratio (1:1.5; 1:2; and 1:3) and variations in backfill height (1m , 2m, 3m and 4m). Results showed that the effectiveness of the foam mortar increased with the increase in the steepness and the height of the backfill material. The analysis results also showed that the greatest increase in the value of the safety factor occurred at backfill height of 4m with a slope ratio of 1:3 to 28.89%, the greatest reduction value in deflection occurred at backfill height of 4m with a slope ratio of 1:3 to 96.2%, and the greatest reduction value in bending moment occurred at backfilling height of 4m with a slope ratio of 1:1.5 to 89.73%..